The beginnings of narrative criticism in Algeria - hadjadj, jsamira; sahouadj, mouhmed (El Omda in Linguistics and Discourse Analysis, 2025)
according to a specific methodological conception. Studies in Algerian criticism, but rather is keen to choose models of critical studies to reveal their critical direction and discuss their visions and the extent to which they represent modern monetary trend